Nintendo’s pursuit for profitability: a pedagogical case study - Almeida, Cláudio R. K. de (2015)
The home video game console industry, like most high technology industries, is characterized by fast innovation, intense competition and a generally volatile environment. Since the mid-1990s, this industry has essentially been dominated by three major companies, Nintendo, Sony and Microsoft. However, in recent years (since 2012) Nintendo’s performance has been below expectations, with revenues falling, negative operating income for the last three years, and falling share prices. As a result, Nintendo’s management has started, especially since the second half of 2014, a concerted effort to improve the company’s fortunes. At the moment these efforts have resulted in better media coverage and a stop in share price fall. It is still early to know if Nintendo’s pursuit for profitability will succeed; nonetheless, it is both of import and interest to understand how companies seek to achieve superior performance, which is why Nintendo was chosen to be analyzed. The aim of this project is to conduct a pedagogical case study on Nintendo, with a focus on how the company is attempting to return to profitability in the midst of intensified competition from its main rivals, Sony and Microsoft, and a growing threat from substitute products, namely mobile gaming. Through the case study and the request for a strategic analysis, the project will present its target audience – management undergraduate students – an opportunity to understand Nintendo and its industry; as well as, give them the chance to put into practice some strategic management concepts and frameworks, which may prove to be useful in both their academic and professional careers.